S23 Optimum diagnostic pathway and pathologic confirmation rate of early stage lung cancer: results from VIOLET. (12th November 2019) - Lim, E; Begum, S; Batchelor, T; Krishnadas, R; Shackcloth, M; Dunning, J; Paul, I; Anikin, V; McGonigle, N; Naidu, B; Fallouh, H; Belcher, E; et al.
Abstract : As pathological confirmation of lung cancer influences treatment selection for suspected early stage lung cancer, high pre-treatment tissue confirmation rates (90%) have been recommended by the National Lung Cancer Audit 2018. However, this practice prior to radical management of patients with early stage lung cancer has never been studied. Using prospective collection of pre-defined biopsy data within multi-disciplinary teams in UK centres, we sought to define the management and outcomes of incomplete pre-treatment tissue confirmation of primary lung cancer in patients undergoing surgery in a multi-centre clinical trial. Methods: VIOLET is an UK National Institute of Healthcare Research (NIHR) Health Technology Assessment (HTA) funded clinical trial (Ref: 13/04/03) comparing video-assisted thoracic surgery (VATS) versus open surgery for known or suspected lung cancer. Diagnostic patient pathways were identified and documented for participants with and without pre-surgical tissue confirmation of primary lung cancer. Methods of tissue confirmation (where undertaken) were documented, with resected pathology report as reference compared against the outcome of inappropriate lobectomy (benign disease or secondary lung cancer). Results: From July 2015 to February 2019 a total of 2, 109 patients were screened, of whom 503 patients were eligible and consented to participate in VIOLET. In total 263 (52%) of patients had a pre-operative pathologic confirmed diagnosis of primary lung cancer. Of the remaining 240 (48%) patients, the majority 205 (85%) did not have a pre-operative biopsy attempted and 35 patients (15%) received a pre-operative non-diagnostic biopsy. Of the 240 patients who entered the operating theatre without pathological confirmation of primary lung cancer, biopsy and frozen section analysis was undertaken in 144 (60%) patients. In the remaining 96 (40%) a lobectomy was undertaken without tissue confirmation (19% of the cohort of 503 trial participants). The overall lobectomy rate for benign disease was 6/503 (1.2%). Conclusions: Our results suggest low levels of inappropriate resection can be achieved with a pre-surgical tissue confirmation rates of approximately 50% through a combination of intra-operative confirmatory biopsy and correct risk estimation of lung cancer. The practice would need to be monitored to ensure acceptable levels are consistently achieved across multi-disciplinary teams caring for patients with suspected primary lung cancer.